Multistage growth and reworking of the Palaeoproterozoic crust in the Bergslagen area, southern Sweden: evidence from U–Pb geochronology - ANDERSSON, ULF B.; HÖGDAHL, KARIN; SJÖSTRÖM, HÅKAN; BERGMAN, STEFAN (Geological Magazine, 2006)
The Svecofennian Domain of the Fennoscandian Shield constitutes a considerable volume of Palaeoproterozoic crustal growth, 2.1–1.86 Ga ago, in between the Archaean craton in the NE and the 1.85–1.65 Ga Transscandinavian Igneous Belt (TIB) in the south and west. The Bergslagen area is a classical ore province located in the southwestern part of the Svecofennian Domain of south-central Sweden. Its northern part is dominated by volcanic and plutonic rocks of a magmatic arc with continental affinity, while the SE part is made up by a sedimentary basin. The Bergslagen area shows a metamorphic zonation from lower to middle amphibolite facies in the north to upper amphibolite facies and locally granulite facies in the south; a small greenschist area exists in the west. Identifying the age spectra of inherited components, magmatic crystallization, as well as metamorphic episodes, provide important constraints on the geodynamic evolution of this centrally located piece of the Shield. U–Pb zircon SIMS data presented in this paper complement the previous, regionally scattered TIMS data from this area. Magmatic zircons from two felsic metavolcanic rocks and two amphibolites (metagabbros) yield 1888±12, 1892±7 and 1887±5, 1895±5 Ma, respectively; i.e. within the 1.91–1.86 Ga range previously obtained for Early Svecofennian magmatism in Bergslagen. An augen gneiss from southern Bergslagen, assigned to the earliest TIB generation, yield an intrusive age of 1855±6 Ma. Metamorphic monazites from the same rock indicate that deformation and elevated thermal activity prevailed 1.83–1.82 Ga ago (TIMS). Metamorphic zircons in high-grade metasedimentary rocks from the south and west yield ages of 1793±5 and 1804±10 Ma, in accordance with ages for regional peak metamorphism and migmatite formation found elsewhere in the southern Svecofennian province of Sweden. More importantly, a few zircon crystals and overgrowths in rocks from the north indicate an early metamorphic episode at c . 1.87 Ga, indicating that Bergslagen has experienced ...